2011
DOI: 10.12968/bjhc.2011.17.11.531
|View full text |Cite
|
Sign up to set email alerts
|

Clinical governance and attention to human resources

Abstract: The role of human resource management in implementing clinical governance framework remains largely unexplored. This article aims to fill this gap in the literature. A qualitative approach has been adopted to develop an insight into the research topic by analysing 35 crucial case studies and documents published by different independent agencies in UK associated with monitoring and evaluating the progress of a major clinical governance framework in the NHS organisations. A human resource strategy designed to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The importance of optimal health human resource management can be considered from the WHO's viewpoint. According to WHO report, a significant proportion of public governmental resources is allocated to healthcare sectors and the most fundamental part is related to health human resources [12][13][14]. A large amount of costs attributed to health human resources is related to the hospitals and health centers.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of optimal health human resource management can be considered from the WHO's viewpoint. According to WHO report, a significant proportion of public governmental resources is allocated to healthcare sectors and the most fundamental part is related to health human resources [12][13][14]. A large amount of costs attributed to health human resources is related to the hospitals and health centers.…”
Section: Introductionmentioning
confidence: 99%
“…The shortage of staff is considered one of the most important challenges in health fields (17). The lack of human resources is a problem that can be seen in clinical environments, leading to extra workload that affects intradisciplinary and interdisciplinary collaboration and the quality of services (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The challenge of a shortage of person-power for implementing clinical governance was observed in many Iranian hospitals [33]. Various studies showed that managers need sufficient human resources to establish a proper system of clinical governance [45, 57].…”
Section: Discussionmentioning
confidence: 99%